Resin composition

CN123022755APending Publication Date: 2026-10-30SUMITOMO CHEM CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580015605.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-21
Filing Date
2025-02-20
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0014]因此,本发明的实施方式的目的在于提供一种具有良好外观且具有充分导热率的树脂组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022755A_ABST
    Figure CN123022755A_ABST
Patent Text Reader

Abstract

The present invention provides a resin composition containing inorganic particles and one or more resins, the inorganic particles comprising one or more amorphous particles as particles having an aspect ratio of less than 0.90, and one or more spherical particles as particles having an aspect ratio of 0.90 or more, the specific gravity difference rate calculated from formula (1) and formula (2) being 2.5% or more and less than 19.7%. Specific gravity difference rate (%) = (1 - SG1 / SG2) x 100 (1);.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to resin compositions containing particles and resin, and more particularly to resin compositions for heat dissipation materials. Background Technology

[0002] Heat generated by energizing electronic components is dissipated via a heat sink. To improve heat dissipation efficiency, techniques are known to fill the space between the electronic components and the heat sink with a heat-dissipating material.

[0003] As one of the heat dissipation materials, there are resin compositions containing resin and inorganic particles. For example, silicon nitride particles (e.g., Patent Document 1), alumina particles (e.g., Patent Document 2), or both (e.g., Patent Document 3) are used as inorganic particles.

[0004] Patent document 1 discloses a liquid sealing resin composition before curing, which has (A) epoxy resin, (B) epoxy resin curing agent and (C) silicon nitride powder as essential components.

[0005] Patent Document 2 discloses a resin composition for liquid sealing before curing, which preferably includes a resin material and a filler made of inorganic material, and uses alumina particles as the filler.

[0006] Patent document 3 discloses a resin composition comprising silicon nitride, spherical thermally conductive particles (alumina particles), and resin. 50% of the silicon nitride particles have a particle size of 0.1–15 μm, and 50% of the alumina particles have a particle size of 10–100 μm. The resin composition contains 2–30% by volume of silicon nitride and 30–80% by volume of alumina particles, with the total content of silicon nitride and alumina particles being 55–85% by volume.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2000-109651

[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-134983

[0011] Patent Document 3: Japanese Patent No. 6508508 Summary of the Invention

[0012] In recent years, resin compositions used in various electronic components have been required to have not only sufficient thermal conductivity but also a good appearance with low light scattering.

[0013] No research was conducted on appearance improvement in the resin compositions disclosed in Patent Documents 1-3.

[0014] Therefore, the object of embodiments of the present invention is to provide a resin composition having a good appearance and sufficient thermal conductivity.

[0015] Scheme 1 of the present invention is a resin composition comprising inorganic particles and one or more resins.

[0016] The inorganic particles include one or more amorphous particles with an aspect ratio less than 0.90, and one or more spherical particles with an aspect ratio greater than 0.90.

[0017] The specific gravity difference calculated by equations (1) and (2) is greater than 2.5% and less than 19.7%.

[0018] Specific gravity difference rate (%) = (1-SG1 / SG2)×100 (1)

[0019]

[0020] In formula (1), SG1 is the specific gravity of the resin composition, and in formula (2), ρa n Va represents the proportion of the nth amorphous particle among the x types of amorphous particles. n ρb is the ratio of the volume of the nth amorphous particle to the total volume of the amorphous particles, the spherical particles, and the resin. m Let Vb be the proportion of the m-th type of spherical particle among the y types of spherical particles. m ρc is the ratio of the volume of the m-th type of spherical particle to the total volume of the amorphous particles, the spherical particles, and the resin. l Vc is the specific gravity of the lth resin in the z-type resins. l The ratio of the volume of the l-th type of resin to the total volume of the amorphous particles, the spherical particles, and the resin is given, where n, m, l, x, y, and z are positive integers.

[0021] Scheme 2 of the present invention is the resin composition described in Scheme 1, wherein when the total amount of the inorganic particles and the resin is set to 100% by volume, the content of the inorganic particles is 55% by volume or more.

[0022] Scheme 3 of the present invention is the resin composition described in Scheme 1 or 2, wherein the amorphous particles are silicon nitride particles, and the inorganic particles contain 45 vol% to 75 vol% of the silicon nitride particles.

[0023] Scheme 4 of the present invention is the resin composition of any one of Schemes 1 to 3, wherein the amorphous particles are silicon nitride particles, the spherical particles are alumina particles, and the volume ratio of the silicon nitride particles to the alumina particles is 0.9 to 3.9.

[0024] Scheme 5 of the present invention is the resin composition of any one of Schemes 1 to 4, wherein the amorphous particles are silicon nitride particles, and the cumulative particle size D50 of the cumulative 50% of the volume-based particle size distribution of the silicon nitride particles from the microparticle side is 1 μm to 250 μm.

[0025] Scheme 6 of the present invention is the resin composition described in any one of Schemes 3 to 5, wherein the β-saturation of the silicon nitride particles is 65% or more.

[0026] According to embodiments of the present invention, a resin composition having a good appearance and sufficient thermal conductivity can be provided. Detailed Implementation

[0027] The inventors conducted extensive research to provide a resin composition with both a good appearance and sufficient thermal conductivity. To achieve a good appearance with minimal light scattering, the inventors conceived of increasing porosity. Specifically, this involved increasing the ratio (“1-SG1 / SG2”×100 (%), hereinafter also referred to as the “specific gravity difference ratio”) between the actual specific gravity of the resin composition (including porosity) SG1 and the specific gravity SG2 calculated from the solid components contained in the resin composition assuming it were porosity-free. However, it was found that simply increasing the specific gravity difference ratio resulted in a decrease in thermal conductivity due to a large number of porosity particles.

[0028] Therefore, the inventors have discovered for the first time that by mixing particles of different morphologies (amorphous particles with an aspect ratio less than 0.90 (hereinafter also referred to as "amorphous particles") and spherical particles with an aspect ratio greater than 0.90 (hereinafter also referred to as "spherical particles")) together as filler particles, it is possible to achieve a resin composition with a large specific gravity difference, good appearance, and sufficient thermal conductivity. This is believed to be because, at a large specific gravity difference, which would normally decrease thermal conductivity, the amorphous particles form a framework, and the spherical particles are positioned between the amorphous particles, thereby creating sufficient thermal conductivity pathways.

[0029] The requirements of this embodiment will be described in detail below.

[0030] [Resin Composition]

[0031] The resin composition involved in this embodiment contains inorganic particles and one or more resins. The inorganic particles include one or more amorphous particles that are particles with an aspect ratio of less than 0.90, and one or more spherical particles that are particles with an aspect ratio of 0.90 or more.

[0032] The specific gravity difference calculated by equations (1) and (2) is greater than 2.5% and less than 19.7%.

[0033] Specific gravity difference rate (%) = (1 - SG1 / SG2) × 100 (1)

[0034]

[0035] In formula (1), SG1 is the specific gravity of the resin composition; in formula (2), SG2 can be the theoretical specific gravity when the porosity of the resin composition is ignored; ρa n Va represents the proportion of the nth amorphous particle among the x types of amorphous particles. n ρb is the ratio of the volume of the nth amorphous particle to the total volume of the amorphous particles, the spherical particles, and the resin. m Let Vb be the proportion of the m-th type of spherical particle among the y types of spherical particles. m ρc is the ratio of the volume of the m-th type of spherical particle to the total volume of the amorphous particles, the spherical particles, and the resin. l Vc is the specific gravity of the lth resin in the z-type resins. l The ratio of the volume of the l-th type of resin to the total volume of the amorphous particles, the spherical particles, and the resin is given, where n, m, l, x, y, and z are positive integers.

[0036] The resin composition has a good appearance and adequate thermal conductivity.

[0037] As inorganic particles, ceramics such as silicon dioxide, alumina, aluminum nitride, boron nitride, silicon nitride, and silicon carbide are preferred. Particles composed of inorganic materials with high thermal conductivity are particularly preferred; for example, particles composed of inorganic materials with a thermal conductivity of 15 W / mK or higher are preferred. As such inorganic materials, ceramics such as alumina, aluminum nitride, boron nitride, silicon nitride, and silicon carbide are preferred. Ceramic particles are preferred among the inorganic particles. Since ceramics have high thermal conductivity, using ceramic particles can improve the heat dissipation performance of the resin composition. Furthermore, when insulating ceramics are used as inorganic particles, short circuits in semiconductor devices can be suppressed. Therefore, insulating ceramic particles are more preferred among the inorganic particles, and more specifically, alumina, aluminum nitride, boron nitride, and silicon nitride are even more preferred. As inorganic particles, it is further preferred that one or more inorganic materials selected from alumina and silicon nitride, which have even higher thermal conductivity, be used.

[0038] As the resin, known resins such as silicone resins, epoxy resins, and acrylic resins can be used. As the type of resin, thermoplastic resins, thermoplastic elastomers, and thermosetting resins can also be selected. It should be noted that one type of resin can be used alone, or two or more types can be used in combination. From the viewpoint of moldability and thermal conductivity, silicone resins are preferred.

[0039] Inorganic particles include amorphous particles with an aspect ratio less than 0.90 and spherical particles with an aspect ratio greater than 0.90. By including both amorphous and spherical particles, the specific gravity difference can be within a desired range, thereby obtaining a resin composition with good appearance and sufficient thermal conductivity. When only amorphous particles and spherical particles are used, even if the specific gravity difference can be within a desired range by adjusting the manufacturing method, it is impossible to achieve a resin composition with good appearance and sufficient thermal conductivity.

[0040] It should be noted that in this specification, "amorphous particles" refers to all particles with an aspect ratio less than 0.90. However, the particles typically used in resin compositions for heat dissipation materials contain almost no particles with an aspect ratio less than 0.10. Therefore, "amorphous particles" in one embodiment can be defined as particles with an aspect ratio of 0.10 or more and less than 0.90. Even in this case, the resin composition of this embodiment may contain a small amount (e.g., less than 10% by mass when all particles are set to 100% by mass) of particles with an aspect ratio less than 0.10.

[0041] Furthermore, in this specification, "spherical particles" refers to all particles with an aspect ratio of 0.90 or greater. Since the maximum aspect ratio is 1.00, the aspect ratio of "spherical particles" can also be expressed as 0.90 to 1.00.

[0042] Amorphous and spherical particles within the resin composition can be distinguished by acquiring cross-sectional SEM images of the resin composition.

[0043] There is no particular limitation on the cross section for SEM observation, but in the case of a sheet-like resin composition, a cross section in the thickness direction is preferred. In the case of a resin composition of any shape, and where the thermal conduction direction can be determined, a cross section in the thermal conduction direction is preferred.

[0044] As for the conditions for capturing cross-sectional SEM images, the magnification is 100 to 100,000 times, and the observation area is, for example, 1000 μm × 2000 μm.

[0045] Image analysis was performed on the cross-sectional SEM images of the resin composition to determine the aspect ratio of the inorganic particles displayed in the images. This allows for the differentiation between amorphous particles with an aspect ratio less than 0.90 and spherical particles with an aspect ratio greater than 0.90.

[0046] The inorganic particles displayed in the cross-sectional SEM image were analyzed using image processing software (such as ImageJ (made by the National Institute of Health)). The maximum particle size of inorganic particle 20 was determined (as its "major axis"), and the particle size in the direction perpendicular to the major axis was taken as the "minor axis". For each inorganic particle, the ratio of the minor axis to the major axis (minor axis / major axis) was taken as the aspect ratio of that inorganic particle.

[0047] The specific gravity difference of the resin composition of this embodiment, calculated by the following formulas (1) and (2), is 2.5% or more and less than 19.7%.

[0048] Specific gravity difference rate (%) = (1-SG1 / SG2)×100 (1)

[0049]

[0050] In formula (1), SG1 is the specific gravity of the resin composition; in formula (2), SG2 can be the theoretical specific gravity when the porosity of the resin composition is ignored; ρa n Va represents the proportion of the nth amorphous particle among the x types of amorphous particles. n ρb is the ratio of the volume of the nth amorphous particle to the total volume of the amorphous particles, the spherical particles, and the resin. m Let Vb be the proportion of the m-th type of spherical particle among the y types of spherical particles. m ρc is the ratio of the volume of the m-th type of spherical particle to the total volume of the amorphous particles, the spherical particles, and the resin. l Vc is the specific gravity of the lth resin in the z-type resins. l The ratio of the volume of the first type of resin to the total volume of the amorphous particles, the spherical particles, and the resin, where n, m, l, x, y, and z are positive integers. For the "type" of amorphous particles (or spherical particles, or resin) mentioned here, different specific gravities are used for different types, for example, when the compositions differ, such as alumina, aluminum nitride, boron nitride, and silicon nitride. For example, the specific gravity of alumina can be 3.90 g / cm³. 3 The specific gravity of aluminum nitride can be 3.30 g / cm³. 3 The specific gravity of boron nitride can be 2.25 g / cm³. 3 The specific gravity of silicon nitride can be 3.19 g / cm³. 3 .

[0051] When the specific gravity difference is 2.5% or more, the amount of voids in the resin composition is not easily reduced, making it easier to achieve a good appearance. The specific gravity difference is preferably 3.0% or more, more preferably 4.5% or more. On the other hand, when the specific gravity difference is less than 19.7%, the amount of voids in the resin composition is not excessive, making it easier to improve thermal conductivity. The specific gravity difference is preferably 15.0% or less, more preferably 12.0% or less, and even more preferably 10.0% or less.

[0052] SG1 and SG2 can be determined by the methods described in the embodiments below.

[0053] When the total amount of inorganic particles and resin is set to 100% by volume, the content of inorganic particles is preferably 55% by volume or more, more preferably 65% ​​by volume or more, and particularly preferably 75% by volume or more. This easily ensures a heat conduction path within the resin composition.

[0054] When the total amount of inorganic particles and resin is set to 100% by volume, the content of inorganic particles is preferably 98% by volume or less, more preferably 95% by volume or less, and even more preferably 93% by volume or less. This allows the resin, acting as a binder, to be contained in an appropriate amount, making it easy to suppress the detachment of inorganic particles from the resin composition. Therefore, it is easy to obtain a resin composition with a desired specific gravity difference.

[0055] The inorganic particles preferably contain 45% by volume or more of amorphous particles, more preferably 50% by volume or more. This facilitates the formation of a framework composed of amorphous particles within the resin composition. On the other hand, the inorganic particles preferably contain 75% by volume or less of amorphous particles. This allows for the inclusion of spherical particles in an appropriate amount, which readily intersect the amorphous particles, enabling the formation of a resin composition with a suitable amount of porosity and easily obtaining a resin composition with the desired specific gravity difference.

[0056] The volume ratio of amorphous particles to spherical particles is preferably 0.9 or more, more preferably 1.0 or more. This facilitates the formation of a framework composed of amorphous particles within the resin composition. Conversely, this volume ratio is preferably 3.9 or less, more preferably 2.5 or less, and even more preferably 2.2 or less. This allows spherical particles to easily remain between the amorphous particles, enabling the formation of a resin composition containing a suitable amount of porosity, and easily obtaining a resin composition with the desired specific gravity difference.

[0057] The cumulative particle size distribution of the amorphous particles, from the microparticle side, representing 50% of the total particle size (D50) is preferably 1 μm or more, more preferably 20 μm or more, further preferably 40 μm or more, and particularly preferably 50 μm or more. This facilitates the formation of a framework composed of amorphous particles within the resin composition. The D50 of the amorphous particles is preferably 250 μm or less, more preferably 200 μm or less. This allows for the inclusion of spherical particles in an appropriate amount, which readily become interspersed among the amorphous particles, resulting in a resin composition containing a suitable amount of porosity and easily obtaining a resin composition with the desired specific gravity difference.

[0058] The D50 of the spherical particles is preferably less than 20 μm, more preferably less than 10 μm, even more preferably less than 8 μm, even more preferably less than 7 μm, and particularly preferably less than 6 μm. Thus, the spherical particles can easily fill the spaces between amorphous particles, forming a resin composition containing an appropriate amount of porosity.

[0059] On the other hand, the D50 of the spherical particles is preferably 0.1 μm or more, more preferably 0.5 μm or more. This makes it easier to form thermally conductive pathways within the resin composition.

[0060] The D50 of the spherical particles is preferably 70% or less of the D50 of the amorphous particles. This allows the relatively large amorphous particles to form a framework, and the relatively small spherical particles to disperse easily in their gaps. As a result, within the resin composition, the amorphous particles form the primary heat conduction paths, while the spherical particles filling the spaces between the amorphous particles form auxiliary heat conduction paths, thus further improving the thermal conductivity of the resin composition. More preferably, the D50 of the spherical particles is 60% or less of the D50 of the amorphous particles, even more preferably 50% or less, and particularly preferably 40% or less.

[0061] On the other hand, the D50 of the spherical particles is preferably 0.001% or more of the D50 of the amorphous particles, and more preferably 0.1% or more of the D50 of the amorphous particles. As a result, the spherical particles can easily form auxiliary heat conduction paths.

[0062] Furthermore, by setting the D50 of the spherical particles to the range described above, a resin composition containing an appropriate amount of voids can be formed, thereby obtaining a resin composition with a good appearance.

[0063] When the resin composition contains a variety of spherical particles, it is preferable that the D50 of all types of spherical particles and the D50 of amorphous particles satisfy the above relationship.

[0064] In this embodiment, the D50 of amorphous and spherical particles can be determined by laser diffraction. Specifically, a laser beam can be irradiated onto particles dispersed in water, and the diffraction can be measured to determine the particle size. The measuring device can be a CILAS 1090L type or similar.

[0065] It should be noted that when determining the D50 of amorphous and spherical particles contained in the resin composition, the amorphous and spherical particles can be removed by dissolving the resin in the resin composition with, for example, an organic solvent, or by thermally decomposing the resin at a temperature of 500°C or higher, and these particles can be used for determination.

[0066] Another method for determining the D50 of amorphous and spherical particles is image analysis. For a resin composition, SEM cross-sectional observation is performed, and image analysis is conducted on all amorphous and spherical particles contained in a specified observation area (e.g., 1000 μm × 2000 μm). Based on the measurement results of their particle size (equivalent circle diameter), the particle size equivalent to D50 can be calculated.

[0067] The average aspect ratio of the amorphous particles is preferably 0.50 or more and less than 0.90, more preferably 0.55 to 0.86, and particularly preferably 0.60 to 0.85. This facilitates the formation of a framework from the amorphous particles.

[0068] Furthermore, the average aspect ratio of the spherical particles is preferably 0.90 to 1.00, more preferably 0.91 to 1.00. This allows the spherical particles to easily fall between the range of amorphous particles.

[0069] It should be noted that the average aspect ratio of each particle is obtained by selecting any 20 particles from the SEM images of each particle and calculating the arithmetic mean of their aspect ratios.

[0070] Amorphous particles are preferably silicon nitride particles, and spherical particles are preferably alumina particles. Since silicon nitride particles and alumina particles are inorganic materials with high thermal conductivity, the thermal conductivity of the resin composition can be further improved by using particles composed of them as fillers.

[0071] For example, SEM-EDX analysis of the cross-section of the resin composition can confirm that the amorphous particles are silicon nitride particles and the spherical particles are alumina particles. Based on the cross-sectional SEM image, the amorphous and spherical particles contained in the resin composition are determined separately, and the elemental mappings obtained in the EDX measurement (e.g., the elemental mappings of Si and Al) are confirmed. Thus, it can be confirmed that the amorphous particles are silicon nitride particles and the spherical particles are alumina particles.

[0072] It should be noted that a small amount of amorphous alumina particles (e.g., less than 10.0% by volume of all alumina particles) and / or a small amount of spherical silicon nitride particles (e.g., less than 10.0% by volume of all silicon nitride particles) may also be present, without affecting the purpose of this embodiment.

[0073] The average aspect ratio of the silicon nitride particles is preferably 0.50 or more and less than 0.90, more preferably 0.55 to 0.86, and particularly preferably 0.60 to 0.85. This facilitates the formation of a framework from the silicon nitride particles.

[0074] The average aspect ratio of the alumina particles is preferably 0.90 to 1.00, more preferably 0.91 to 1.00. This allows the alumina particles to easily intersect with the silicon nitride particles, forming a resin composition containing a suitable amount of porosity.

[0075] It should be noted that the average aspect ratio of each particle is obtained by selecting any 20 particles from the SEM images of each particle and calculating the arithmetic mean of their aspect ratios.

[0076] As alumina particles, only one type of alumina particle can be used, or a mixture of alumina particles with different D50 can be used.

[0077] In this specification, when using mixed alumina particles containing two alumina particles with different D50, the alumina particle with the larger D50 is sometimes referred to as the "first alumina particle" and the alumina particle with the smaller D50 is referred to as the "second alumina particle".

[0078] The D50 of the first alumina particles is preferably 3 μm to 10 μm, and the D50 of the second alumina particles is preferably 0.01 μm to 2 μm. Therefore, alumina particles are more likely to be intermediate between silicon nitride particles, making it easier to form a resin composition containing an appropriate amount of porosity.

[0079] The ratio (mixing ratio) of the content (volume %) of the first alumina particles to the second alumina particles is preferably 90:10 to 10:90, more preferably 20:80 to 80:20, further preferably 30:70 to 70:30, and particularly preferably 40:60 to 60:40.

[0080] The β-saturation of the silicon nitride particles is preferably 65% ​​or higher, thereby increasing the thermal conductivity of the silicon nitride particles 20, which in turn further improves the thermal conductivity of the resin composition 10 containing silicon nitride particles 20.

[0081] The β-saturation rate is more preferably 70% or more, further preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more. The β-saturation rate of the silicon nitride particles can be 100% or less.

[0082] In this specification, "β-type silicon nitride content" refers to the percentage (by volume) of β-type silicon nitride contained in silicon nitride particles relative to all silicon nitride.

[0083] When calculating the β-concentration, silicon nitride particles were measured by powder X-ray diffraction and the diffraction pattern was analyzed using the Gazzara & Messier method (GPGazzara and DPMessier, “Determination of Phase Content of Si3N4 by X-ray Diffraction Analysis”, Am. Ceram. Soc. Bull., 56[9]777-80 (1977)).

[0084] Although the physical properties of silicon nitride particles and alumina particles can be determined in the presence of a resin composition containing these particles, if it is difficult to determine them in the presence of a resin composition, the silicon nitride particles and alumina particles can be separated from the resin composition and then determined.

[0085] As a method for separating silicon nitride particles and alumina particles from a resin composition, the resin contained in the resin composition is first dissolved in, for example, an organic solvent, or removed by thermal decomposition at a temperature of 500°C or higher. The resulting mixture of silicon nitride particles and alumina particles is then separated based on differences in specific gravity, particle size, etc. Separation methods based on specific gravity differences include sedimentation or centrifugation in a liquid, dry sieving, or the use of a gravity separation device.

[0086] Furthermore, these resin compositions may be appropriately combined, either alone or in combination with two or more known additives such as plasticizers, curing accelerators, coupling agents, fillers, pigments, flame retardants, antioxidants, surfactants, compatibilizers, weathering agents, antiblocking agents, antistatic agents, leveling agents, and release agents, as needed and within the range that does not impair the effects of this embodiment.

[0087] In one embodiment of the present invention, the thermal conductivity of the resin composition is preferably 5.0 W / (m·K) or higher, more preferably 5.8 W / (m·K) or higher, and even more preferably 6.5 W / (m·K) or higher. When the thermal conductivity of the resin composition is above the aforementioned lower limit, it can have sufficient heat dissipation when used in electronic components. The thermal conductivity of the resin composition can be determined, for example, by the method described in the examples below.

[0088] [Method for manufacturing the resin composition]

[0089] The method for manufacturing the resin composition of this embodiment will be described.

[0090] The resin composition of this embodiment can be obtained by using amorphous particles and spherical particles as inorganic particles and applying known methods to them. For example, when the resin is liquid (e.g., liquid silicone resin), the resin composition can be obtained by mixing the liquid resin, amorphous particles 1, spherical particles and a curing agent, and then curing it using heat or ultraviolet light. The curing agent, mixing method and curing method can be known substances and methods.

[0091] When the resin is solid, the target resin composition can be obtained by mixing amorphous particles, spherical particles and resin, and then mixing them using known methods such as melt mixing.

[0092] The amorphous particles (e.g., silicon nitride particles) used in the manufacturing method of the resin composition can be manufactured by, for example, the methods described later.

[0093] The spherical particles (e.g., alumina particles) used in the resin composition manufacturing method may be, for example, commercially available spherical alumina particles, or spherical alumina particles manufactured by a known method (e.g., flame melting).

[0094] As an example of a method for manufacturing amorphous particles used in a resin composition manufacturing process, a method for manufacturing silicon nitride particles will be described.

[0095] Regarding silicon nitride particles, including:

[0096] (1) The process of synthesizing silicon nitride composite crystals by combustion synthesis using Si-containing raw materials under a nitrogen atmosphere.

[0097] (2) The process of breaking down silicon nitride composite crystals to obtain coarse silicon nitride powder.

[0098] (3) The process of micronizing coarse silicon nitride powder to obtain fine silicon nitride powder, and

[0099] (4) The process of heat-treating silicon nitride micro powder to obtain silicon nitride particles.

[0100] • Process (1): The process of synthesizing silicon nitride composite crystals

[0101] As a Si-containing raw material, Si powder is used, for example.

[0102] The D50 of the raw material Si is, for example, in the range of 2~10 μm. This allows for the suppression of oxygen impurities, while simultaneously increasing the combustion rate and thus raising the synthesis temperature, resulting in good crystal growth. As an example, the D50 of Si is 5 μm.

[0103] A diluent is used to adjust the Si content in the mixed raw materials. As a diluent, separately prepared silicon nitride particles are used. This diluent can be any of α-type silicon nitride particles or β-type silicon nitride particles, or a mixture thereof. The D50 of the diluent is preferably in the range of 0.5 to 2.0 μm. As an example, the D50 of the diluent is 1.0 μm. The amount of diluent added relative to all raw materials (including the diluent) is less than 10% by mass. As an example, the diluent is added at 5 to 8% by mass relative to all raw materials. By keeping the amount of diluent added within the above range, the desired amount of silicon nitride particles used in the resin composition of this embodiment can be produced in a specified quantity.

[0104] In this embodiment, raw material Si and a diluent are mixed and filled into an insulated and heat-resistant container. The thermal conductivity of this container is below 1 W / mK, and the material can be alumina or zirconium oxide, but carbon is preferred to account for impurities. After filling, the container is covered with a lid made of the same material as the insulated and heat-resistant container. Furthermore, to increase the internal temperature of the synthesized body during combustion, the thickness of the mixed raw material is greater than 100 mm, preferably greater than 100 mm and less than 150 mm. Combustion synthesis is carried out under a nitrogen atmosphere in the range of 0.5 to 1 MPa (e.g., 0.9 MPa). By adjusting the pressure range within the above range, efficient synthesis can be achieved while suppressing the increase in equipment costs.

[0105] When filling the crucible with the mixed raw materials, a layer of powder (silicon nitride) with a thickness of 1 mm to 80 mm is laid on the bottom and sides of the crucible, and then the mixed raw materials are filled in, and the upper surface is covered with a layer of powder with a thickness of 1 mm to 80 mm. By covering the entire surface with powder, the mixed raw materials can be kept warm, and the desired silicon nitride particles used in the resin composition of this embodiment can be produced in a specified amount.

[0106] To more effectively promote crystal growth, catalysts can also be used, such as adding approximately 0.01 to 0.1% by mass of Y₂O₃, Fe₂O₃, CaO, Ni, Co, C, etc. Furthermore, external auxiliary heating in the range of 500°C to 1700°C (e.g., 1500°C) or combustion synthesis based on auto-ignition can also increase the combustion temperature.

[0107] • Process (2): The process of obtaining coarse silicon nitride powder

[0108] Silicon nitride composite crystals are a form formed by the aggregation of multiple silicon nitride particles. In step (2), coarse silicon nitride powder is obtained by breaking down the silicon nitride composite crystals. For example, the composite crystals are broken down using a general coarse crushing device such as a hammer mill or disc mill until they pass through a sieve with a specified mesh size (e.g., a sieve with a mesh size in the range of 400μm to 500μm).

[0109] • Process (3): The process of obtaining silicon nitride micro powder

[0110] Silicon nitride coarse powder is further finely ground to obtain finely ground silicon nitride powder. Fine grinding is performed using a fine grinding device such as a ball mill. The obtained finely ground powder can be classified as needed. Classification can be performed by sieving, wet classification, etc.

[0111] • Process (4): The process of obtaining silicon nitride particles

[0112] Silicon nitride particles are obtained by heat treatment of micronized silicon nitride powder. The heat treatment forms an oxide film on the surface of the silicon nitride particles, thus stabilizing them chemically. The heat treatment is carried out at atmospheric temperature between 500°C and 1200°C. The heat treatment time can be adjusted appropriately according to the heat treatment temperature. For example, a heat treatment time of 5 hours.

[0113] In the method for manufacturing silicon nitride particles, silicon nitride composite crystals are synthesized by utilizing the reaction heat of combustion synthesis, and then broken down, graded, and micronized to produce the silicon nitride particles of this embodiment.

[0114] Example

[0115] Hereinafter, this embodiment will be described in detail through examples implemented to illustrate its effects. It should be noted that this embodiment is not limited to any of the examples below.

[0116] <Production of Silicon Nitride Particles>

[0117] Si powder (D50 = 5 μm) and separately prepared silicon nitride powder (D50 = 1 μm) as a diluent were mixed using a rolling ball mill. The amount of diluent added was 5-8% by mass relative to all raw materials (including diluent). The mixed powder was filled into a carbonaceous heat-resistant insulated container with a powder coating of 1 mm to 80 mm thickness on the bottom and sides, making the raw material layer thickness greater than 100 mm and less than 150 mm. Then, the raw material layer was covered with a powder coating of more than 1 mm and less than 80 mm thickness. Then, a lid made of carbonaceous heat-resistant insulated material was placed on top, and synthesis was carried out under a nitrogen atmosphere of 0.9 MPa. After synthesis, the powder was coarsely pulverized (crushed) in a mortar until it passed through a sieve with specified mesh size.

[0118] The coarsely ground powder was then finely ground using a ball mill. The finely ground powder was then sieved and classified using a vibrating screen, followed by wet classification to obtain silicon nitride particles A to F.

[0119] • When sieving using a sieve with a mesh size of 150 μm, the silicon nitride particles A remaining on the sieve (D50 is 192.0 μm)

[0120] • When sieving using a sieve with a mesh size of 150 μm, the powder remaining on the sieve is further sieved using a sieve with a mesh size of 106 μm. The silicon nitride particles B remaining on the sieve have a D50 of 118.0 μm.

[0121] • When sieving using a 106μm sieve, the powder remaining on the sieve is further sieved using a 75μm sieve. The silicon nitride particles C remaining on the sieve have a D50 of 83.0μm.

[0122] • When sieving using a 75μm sieve, the powder remaining on the sieve is further sieved using a 63μm sieve. The silicon nitride particles remaining on the sieve are D (D50 is 58.0μm).

[0123] • When sieving using a sieve with a mesh size of 75 μm, the silicon nitride particles E remaining on the sieve (D50 is 22.0 μm)

[0124] • Silicon nitride particles F (D50 is 56.0 μm) are formed by mixing silicon nitride particles C, D and E.

[0125] <Preparation of Alumina Particles>

[0126] Three types of alumina particles were prepared. The first type of alumina particle used was Denka's DAW-05, the second type was Sumitomo Chemical Co., Ltd.'s AA-04, and the third type was Denka's DAW-120.

[0127] The mixed alumina particles obtained by mixing the first to third alumina particles in a specified ratio are used as "alumina particles".

[0128] Various measurements were performed on silicon nitride particles A to F and first to third alumina particles.

[0129] <Determination of D50 of each particle>

[0130] The particle size distribution of silicon nitride and aluminum oxide particles was determined, and the D50 of each particle was calculated.

[0131] The particle size distribution was determined using laser diffraction. A laser beam was irradiated onto the sample dispersed in water, and the diffraction was measured to determine the particle size. A CILAS 1090L model was used for the measurement. The particle size was calculated using the equivalent circular diameter. The equivalent circular diameter refers to the diameter of a perfect circle with the same area as the projected particle image. Furthermore, the particle size D50 was set as the reference for volume.

[0132] The D50 values ​​of each particle are shown in Table 2.

[0133] The D50 of the mixed alumina particles (a mixture of first alumina particles, second alumina particles, and / or third alumina particles) was not determined. However, in the mixture of first alumina particles and second alumina particles, based on the D50 of the first alumina particles (6.0 μm) and the D50 of the second alumina particles (0.5 μm) before mixing, it can be said that the D50 of the mixed alumina particles is below 6.0 μm.

[0134] <Determination of the aspect ratio of each particle>

[0135] SEM images were taken of silicon nitride particles, first alumina particles, and second alumina particles respectively. The following equipment was used for the imaging.

[0136] • Use of equipment

[0137] Scanning electron microscope: Helios G4 UX (manufactured by FEI Corporation, Japan)

[0138] The shooting conditions are as follows.

[0139] Accelerating voltage: 5.0kV

[0140] Signal: BSE

[0141] Irradiation current: 0.1 nA

[0142] Shooting magnification: 250x (particles with D50 greater than 20μm), 1000x (particles with D50 less than 20μm), 100000x (particles with D50 less than 1μm).

[0143] The aspect ratio of all particles in the SEM image was determined using the image processing software ImageJ (made by the National Institute of Health). First, the largest particle diameter was taken as the major axis, and the particle diameter in the direction orthogonal to the major axis was taken as the minor axis. The major and minor axes of each particle were measured, and then the ratio of the minor axis to the major axis (minor axis / major axis) was calculated.

[0144] The above measurement results show that all silicon nitride particles are particles with an aspect ratio of less than 0.90 (i.e., amorphous particles), and all first alumina particles and all second alumina particles are particles with an aspect ratio of more than 0.90 (i.e., spherical particles).

[0145] As a reference for understanding the aspect ratio of each particle, the average aspect ratio of each particle was calculated. The average aspect ratio of each particle was obtained by selecting any 20 particles from the SEM images of each particle and taking the arithmetic mean of the aspect ratios of these particles.

[0146] The results of the measurement of the average aspect ratio of silicon nitride particles are shown in Table 2.

[0147] The average aspect ratio of the first and third alumina particles is 0.97, and the average aspect ratio of the second alumina particle is 0.91.

[0148] <Determination of β-saturation of silicon nitride particles>

[0149] The diffraction pattern of silicon nitride particles was obtained using a powder X-ray diffraction apparatus (Rigaku Electron). The measurement conditions are as follows.

[0150] X-ray source: CuKα rays

[0151] X-ray output: 45kV, 200mA

[0152] Graphite monochromator

[0153] • Diffraction angle (2θ): Step scan in 0.02° increments within the range of 2–90°.

[0154] • Scanning speed: 21.7 deg / minute

[0155] When silicon nitride particles contain components other than silicon nitride, the proportions of these components are determined by comparing their peaks with the corresponding peaks of a standard sample. The resulting powder X-ray diffraction pattern confirms that all silicon nitride particles consist only of α-type and β-type silicon nitride. Based on this, the proportion of β-type silicon nitride in the sample (β-type ratio) is calculated using the Gazzara & Messier method.

[0156] The calculation results are shown in Table 2.

[0157] <Preparation of Resin Composition>

[0158] The various particles (silicon nitride particles, first alumina particles, second alumina particles, and third alumina particles) are combined in the silicone resin (main agent: DOWSIL (trademark) CY 52-276 A manufactured by Dow Company, curing agent: DOWSIL (trademark) CY 52-276 B manufactured by Dow Company).

[0159] The proportions of each particle and the silicon nitride / alumina particle ratio are shown in Table 2. It should be noted that samples No. 1-6 and 8 did not contain alumina particles, and sample No. 7 did not contain silicon nitride particles.

[0160] A liquid resin composition was obtained by mixing silicone resin and each particle in a ratio of 20% by volume and a total content of 80% by volume of all particles using defoaming agent Rintaro (Thinky Co., Ltd.).

[0161] As a mold, a mold with 1cm × 10cm rectangular holes was made in an aluminum plate with a thickness of 1mm. A transparent PET film coated with release agent (back side film) was attached to the back side of the mold, with the release agent coating side in contact with the mold, thus covering the rectangular holes. 3g of liquid resin composition (gray) was injected into the rectangular holes of the mold, and then a transparent PET film coated with release agent (surface side film) was attached from above, with the release agent coating side in contact with the mold and the resin composition. Then, a metal roller was used to gently press the resin composition into the rectangular holes of the mold from above the surface side film, forming a 1cm × 10cm strip. Another aluminum plate was then placed on top, and the mixture was heated at 120°C for 8 hours and allowed to stand to cure the resin.

[0162] After curing, allow the aluminum plate to cool down to around room temperature. Then, peel off two PET films from both sides of the cured resin composition to obtain the sheet-like resin composition for testing.

[0163] <Determination of Specific Gravity Difference of Resin Composition>

[0164] To determine the measured value of the specific gravity SG1, the specific gravity of the sheet resin composition prepared according to the above steps is calculated.

[0165] Density was measured using an electronic hydrometer MDS-300 (manufactured by ALFA MIRAGE Co., Ltd.).

[0166] Density is determined by Archimedes' method (solid density determination) according to the following formula. Specific gravity SG1 is then determined from the density.

[0167] ρ=A÷(A-B)×(ρ0-ρ L ) + ρ L

[0168] in,

[0169] ρ: Density of the sheet resin composition

[0170] A: Weight of the sheet-like resin composition measured in the atmosphere.

[0171] B: Weight of the sheet-like resin composition determined in the replacement solution (water)

[0172] ρ0: Density of the replacement fluid (water) (1.0000 g / cm³) 3 )

[0173] ρ L Atmospheric density (0.0012 g / cm³) 3 ).

[0174] The specific gravity SG2 is calculated according to the above formula (2). It should be noted that x=1, y=3, z=1, ρa1 is the specific gravity of silicon nitride, ρb1 (specific gravity of the first alumina particle), ρb2 (specific gravity of the second alumina particle) and ρb3 (specific gravity of the third alumina particle) are the specific gravity of alumina, and ρc1 is the specific gravity of the organosilicon resin, using the values ​​shown in Table 1. It should be noted that, for reference, Table 1 also records the specific gravity of materials that can be used as amorphous particles (aluminum nitride, boron nitride).

[0175]

[0176] The specific gravity difference rate of the resin composition was obtained from the above formula (1) and is shown in Table 2.

[0177] <Determination of thermal conductivity of resin compositions>

[0178] The thermal diffusivity and specific heat of the obtained sheet-like resin composition were measured, and the thermal conductivity was determined.

[0179] For thermal diffusivity, a test sample measuring 10 mm long × 10 mm wide × 0.5 mm thick was prepared from the above-mentioned sheet resin composition and measured at room temperature using temperature wave thermal analysis (TWA). The measuring apparatus used was the ai-Phase Mobile manufactured by ai-Phase Corporation.

[0180] For thermal diffusivity, measurements are taken at any three points on a single test sample, and the average value is calculated from the results of these three points as the measured value.

[0181] The specific heat of the resin composition is calculated based on the proportions of the resin and each particle. The specific heat of the silicone resin is 0.98 (kJ / (kg·K)), the specific heat of the silicon nitride particles is 0.67 (kJ / (kg·K)), and the specific heat of the alumina particles is 0.75 (kJ / (kg·K)).

[0182] Substitute the measured thermal diffusivity and specific heat, as well as the density results measured in the above <Determination of the specific gravity difference of the resin composition>, into the following formula to calculate the thermal conductivity, as shown in Table 2.

[0183] Thermal conductivity = thermal diffusivity × specific heat × density

[0184] <Appearance Evaluation of Resin Compositions>

[0185] The appearance of the above-mentioned sheet resin composition was confirmed at an illumination of 1000 lx and evaluated according to the following criteria, with A being deemed acceptable.

[0186] A: The surface has weak light scattering and a good appearance.

[0187] B: The surface scatters light strongly.

[0188] C: The surface scatters light more strongly.

[0189]

[0190] The results in Table 2 will be discussed below.

[0191] The resin compositions of samples No. 1 to 6, which meet the requirements of this embodiment, have a good appearance and sufficient thermal conductivity. On the other hand, the resin compositions of samples No. 7 and 8, which do not meet the requirements of this embodiment, have poor appearance and poor thermal conductivity.

[0192] This application claims priority to Japanese Patent Application No. 2024-024843, filed on February 21, 2024. Japanese Patent Application No. 2024-024843 is incorporated herein by reference.

Claims

1. A resin composition comprising inorganic particles and one or more resins, The inorganic particles include one or more amorphous particles with an aspect ratio less than 0.90, and one or more spherical particles with an aspect ratio greater than 0.

90. The specific gravity difference calculated by equations (1) and (2) is greater than 2.5% and less than 19.7%. Specific gravity difference rate (%) = (1 - SG1 / SG2) × 100 (1) In formula (1), SG1 is the specific gravity of the resin composition, and in formula (2), ρa n Va represents the proportion of the nth amorphous particle among the x types of amorphous particles. n ρb is the ratio of the volume of the nth amorphous particle to the total volume of the amorphous particles, the spherical particles, and the resin. m Let Vb be the proportion of the m-th type of spherical particle among the y types of spherical particles. m ρc is the ratio of the volume of the m-th type of spherical particle to the total volume of the amorphous particles, the spherical particles, and the resin. l Vc is the specific gravity of the lth resin in the z-type resins. l The ratio of the volume of the l-th type of resin to the total volume of the amorphous particles, the spherical particles, and the resin is given, where n, m, l, x, y, and z are positive integers.

2. The resin composition according to claim 1, wherein, When the total amount of the inorganic particles and the resin is set to 100% by volume, the content of the inorganic particles is 55% by volume or more.

3. The resin composition according to claim 1, wherein, The amorphous particles are silicon nitride particles, and the inorganic particles contain 45% to 75% by volume of the silicon nitride particles.

4. The resin composition according to claim 1, wherein, The amorphous particles are silicon nitride particles, the spherical particles are aluminum oxide particles, and the volume ratio of silicon nitride particles to aluminum oxide particles is 0.9 to 3.

9.

5. The resin composition according to claim 1, wherein, The amorphous particles are silicon nitride particles, and the cumulative particle size distribution of the silicon nitride particles, with the cumulative 50% particle size D50 from the microparticle side being 1 μm to 250 μm, is as follows:

6. The resin composition according to any one of claims 3 to 5, wherein, The β-saturation of the silicon nitride particles is above 65%.

Citation Information

Patent Citations

  • Liquid sealing resin composition

    JP2000109651A

  • Insulation layer forming composition, insulation layer forming film, and substrate

    JP2013134983A

  • Carbon dioxide adsorbent for pressure swing method

    JP2024024843A